The Ubiquitin Receptor DA1 Regulates Seed and Organ Size by Modulating the Stability of the Ubiquitin-Specific Protease UBP15/SOD2 in Arabidopsis . Issue 2 (28th February 2014) - Du, Liang; Li, Na; Chen, Liangliang; Xu, Yingxiu; Li, Yu; Zhang, Yueying; Li, Chuanyou; Li, Yunhai
Abstract : This work shows that the ubiquitin receptor DA1 genetically and physically interacts with the ubiquitin-specific protease UBP15 to regulate seed size in Arabidopsis, suggesting that DA1 and UBP15 are promising targets for crop improvement. Abstract: Although the control of organ size is a fundamental question in developmental biology, little is known about the genetic and molecular mechanisms that determine the final size of seeds in plants. We previously demonstrated that the ubiquitin receptor DA1 acts synergistically with the E3 ubiquitin ligases DA2 and ENHANCER1 OF DA1 (EOD1)/BIG BROTHER to restrict seed growth in Arabidopsis thaliana . Here, we describe UBIQUITIN-SPECIFIC PROTEASE15 (UBP15), encoded by SUPPRESSOR2 OF DA1 ( SOD2 ), which acts maternally to regulate seed size by promoting cell proliferation in the integuments of ovules and developing seeds. The sod2/ubp15 mutants form small seeds, while overexpression of UBP15 increases seed size of wild-type plants. Genetic analyses indicate that UBP15 functions antagonistically in a common pathway with DA1 to influence seed size, but does so independently of DA2 and EOD1 . Further results reveal that DA1 physically associates with UBP15 in vitro and in vivo and modulates the stability of UBP15. Therefore, our findings establish a genetic and molecular framework for the regulation of seed size by four ubiquitin-related proteins DA1, DA2, EOD1, and UBP15 and suggest that they are promising targets for increasing seed size in crops.